THE ANALYSIS OF DECISION OF SHARIA BANKING STUDY PROGRAM STUDENTS USING SAVINGS PRODUCTS IN CONVENTIONAL BANK - Efrin Canella; Deky Anwar; M. Iqbal (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
This article is entitled Analysis of Decisions by Students of Islamic Banking Study Program Using Products in Conventional Banks (Case Study of Sharia Banking Study Program Students at UIN Raden Fatah Palembang Class of 2017-2018). This research is motivated by students who are still using savings products in conventional banks, therefore the purpose of this research is to find out the factors and causes or reasons that can influence the decisions of students majoring in Islamic banking to use Savings Products at Conventional Banks, which they should using Savings Products at Islamic Banks. In this study, a qualitative descriptive approach was used, the technique for collecting data was the field method. This study uses data namely, primary data by obtaining it through documentation and interviews with 2017-2018 students, other data in this study are secondary data obtained from primary books which are considered representative or representative of the research as complementary data from primary data. Based on the analysis of research conducted on students who use conventional bank products on the basis of awareness of the inappropriate use of Islamic banks, some respondents said that conventional bank products are more than Islamic banks, which only look at the physical side, not religiously, as said respondent, According to him, conventional bank savings products are easier to reach and the facilities are easy to find and available everywhere, even though there is an administrative fee every month, it's not a problem. From the conclusions obtained based on the results of the decisions of students of UIN Raden Fatah Palembang Islamic Banking Department Class of 2017 and 2018 who use savings products at conventional banks, namely consumer behavior consisting of consumer decision makers, consumers who like all-knowing, consumers who like discounts, consumers in making decisions. decisions but wrong As well as factors that relate directly to the Marketing Mix which consists of a Product, Price, Location, Promotion.